DISCOURSE DEPUTY REGENT OF SAMPANG IN 2017 IN MUSREMBANG LEADERSHIP - Chakim, Abdul (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2019)
The 2017 Musrenbang Kabupaten was led by a vice Bupati. Because of the health condition, Bupati of Sampang cannot be present and leading the forum. The vice Bupati must show his leadership model as if he is the main leader. The success of Musrenbang forum depends on how a Bupati can manage, cooperate and lead all the participants in this forum. This study is to analyze the leadership discourse from 2017 Musrenbang Kabupten Speech Text and relevant literature. The methodology in this study is using discourse analysis. Then, it is led to Van Dijk Model Analysis. This model concerns on three part analyses. They are textual, social cognition and social context analyses. While textual analysis is based on the speech text, social cognition and context analyses are based on the external and what is behind of a discourse. Then, the result of this study is led to what kind of leadership model is showed by Vice Bupati of Sampang in Musrenbang Speech Text and why this speech text (concerned on the content) is produced. First, leadership model can be seen from the textual context in speech text. Second, why this speech text can be produced can be seen from the social cognition and context. So, the three approaches from Van Dijk Model Analysis can lead to two conclusions. They are the kind of leadership model and the background production of this speech text. The result of this study hopefully can be considered as a set of recommendation for the next Bupati in 2019